Functional role of miR-138-5p and miR-200b-3p in testicular germ cell tumors: molecular insights into seminoma and teratoma pathogenesis - Hooshiar, Fatemeh; Azizi, Hossein; Masoudi, Mahla; Skutella, Thomas (International journal of molecular sciences, 2025)
This study aims to investigate the molecular mechanisms underlying germ cell tumors (GCTs), focusing specifically on seminomas and teratomas. By analy...